Nationwide use of psychotropic drugs for treatment of self-reported depression in the Brazilian urban adult population - Luiz Roberto Ramos; Jair de Jesus Mari; Andréia Turmina Fontanella; Tatiane da Silva Dal Pizzol; Andréa Dâmaso Bertoldi; Sotero Serrate Mengue (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Objective: Antidepressant use is increasing worldwide, but national data on psychotropic drug use by depressed patients in Brazil is lacking. Methodology: Between 2013 and 2014, a representative sample of urban adult individuals were asked if they had a diagnosis of chronic disease, had a medical indication for drug treatment, and were taking chronic medications at the time for each reported diagnosis. We analyzed the frequencies of reported depression and the medications related to this disease. Results: Overall, 6.1% of respondents reported depression. The prevalence increased with age - 9.5% among the elders - was higher among women (8.9%) and in the south of the country (8.9%). As a single disease, the prevalence of depression was higher among young people (17.6%). Among those with multimorbidity, the prevalence of depression rose to 25.7%. Of those who reported depression, 81.3% had medical indication for treatment and 90.3% were under treatment - this proportion was lower among young people (84.5%) and those living in the poorest region (78.6%). Antidepressants accounted for 47.2% of psychotropic drugs taken by respondents with depression, with regional differences - only 30% used antidepressants in the North. Polypharmacy was reported by 22% of those with depression and other chronic diseases. Conclusion: Depression in Brazil, is common among young adults as a single chronic disease and highly prevalent among people with chronic multimorbidity, especially the young. The treatment gap was larger among young people and in the less developed regions of the country.